Application of Tens and William Flexion Exercise in Patients With Non Spesific Low Back Pain - Fahruddin, Sri Gunda Fahriana; Inayah, Rizqi Nurul; Yani, Sri (Griya Eka Sejahtera, 2025)
Background: Non-Specific Low Back Pain is a musculoskeletal disorder caused by abnormalities or dysfunctions in musculoskeletal structures without any neurological involvement. This condition is most commonly found in workplaces, especially among individuals who perform activities with incorrect body posture. Non-specific LBP may result from muscle strain or lack of spinal movement, which leads to weakened or tense back muscles.Methods: This study aims to determine the physiotherapy management using a combination of Transcutaneous Electrical Nerve Stimulation (TENS) and William Flexion Exercises in reducing pain and improving mobility in patients with non-specific low back pain. The study employs a descriptive quantitative approach with a case study design. TENS was applied to the lumbar area for 15–20 minutes using conventional frequency, combined with progressively performed William Flexion Exercises over a period of two weeks. Pain was assessed using the Visual Analog Scale (VAS), and functional ability was evaluated using the Oswestry Disability Index (ODI).Results: The results showed a significant reduction in pain levels based on VAS scores and an improvement in functional ability as indicated by ODI scores after the combined therapy.Conclusion: The combination of TENS and William Flexion Exercises is effective in reducing pain and improving function in patients with Non-Specific Low Back Pain.